Cerebrovascular disease, multiple sclerosis, or both? Case report and review of the challenging distinction between two potentially synergistic syndromes - Paola Suarez; Lucas Restrepo (Cerebral Circulation - Cognition and Behavior, 2021)
White matter changes (WMC) are frequently observed in clinical practice, but their clinical relevance is often obscured by radiology reports that do not clearly convey a likely diagnosis. In this regard, two attitudes contribute to diagnostic confusion: a tendency to dismiss findings as trivial (i.e., using vague characterizations such as “non-specific” or “normal for age”), and a gratuitous dilatation of the differential diagnosis (i.e., routinely adding rare diseases to the list, such as vasculitis). Very often, the finding of WMC presents physicians with a very practical problem, which is to determine whether the underlying etiology is an autoimmune demyelinating disease such as multiple sclerosis (MS), or a vasculopathy such as small vessel cerebrovascular disease (SVCVD). The implications of this distinction are great, because the treatment and prognosis of these two syndromes are very different. Here, we describe the challenging case of a relatively young woman with dementia due to a combination of MS and cerebrovascular disease.